AKUNTABILITAS DAN TRANSPARANSI LAPORAN PENGGUNAAN DANA DESA KEPADA MASYARAKAT DI DESA KASIKAN KECAMATAN TAPUNG HULU KABUPATEN KAMPAR PROVINSI RIAU - Muzaki, M. Abd.; Indra, Mexsasai; Tiaraputri, Adi (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Hukum, 2021)
Accountability and openness are forms that are pursued in creating good governance. The accountability that must be carried out by the government is an embodiment of efforts to provide information related to every action or activity of government administration that has village finances. In this case, it cannot be separated from both the central government to the smallest level, namely the village government which is the focus of this research. As for the form of village government accountability in the form of an obligation to provide transparency in the form of budget realization, realization of activities, remaining budget and address of complaints to the village community as stated in article 72 of the minister of home affairs regulation number 20 of 2018 concerning village financial management. However, in this case, the village government of Kasikan, Tapung Hulu Subdrict, Kampar District, has not implemented it optimally.This type of research is a sociological juridical which emphasizes a research approach to the legal aspects related to the subject matter to be discussed, related to the facts or facts in the research location. This research was conducted in Kasikan Village, Tapung Hulu District, Kampar District, Riau Province. By conducting research in the Kasikan village government, the Kasikan Village Consultative Body, Customary Figures, PKK, and Kasikan Village Communities.In the result, there are three main points that can be concluded. First, the accountability and tranaprency of reports on the use of village finances to the community carried out by the kasikan village government have not been implemented properly according to the mechanism in accordance with applicable regulations. Second, the inhibiting factor in implementing the fulfillment of community rigths related to village finances by the village government is due to the wide area of the kasikan village, inadequate human resources, weak community participation, and inadequate facilities and infrastructure in village administration. And third, efforts to fulfill village financial reporting obligations to the community by the village government are only carried out in the form of banners and billboards in front of the kasikan village office. However, the village government will strive to increase community participation and further increase the suvervision of the village consultative body.Keyword: Accountability-Financial-Village